PENGARUH PEMANFAATAN MEDIA GOOGLE CLASSROOM TERHADAP HASIL BELAJAR PKN SISWA KELAS XI DI SMA N 1 KAMPAR - Hasnur Hazima; Supentri Supentri; Separen Separen (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research was motivated by the entry of the covid-19 virus into Indonesia, which caused the paralysis of the economy, education, and social interaction. In the education sector, students study at home using a variety of media, including Google Classroom media. By using this media affect the enthusiasm of students in the teaching and learning process and can improve student learning outcomes. The formulation of the problem raised in this study is whether there is an effect of using classroom media on the learning outcomes of class XI students at SMA Negeri 1 Kampar. The purpose of this study was to determine the effect of the use of classroom media on the results of civic education for class XI students at SMA Negeri 1 Kampar. This research is quantitative through simple linear regression data analysis method with the help of SPSS 23. This study uses data collection techniques through observation, questionnaires (questionnaire) and Library Research. To take the sample, this study used a random sampling technique with a sample of 76 students from class XI. Based on the results of the study, it can be seen that the use of google classroom media is at a low level. Based on the results of the processing of this research data, the results of the product moment correlation analysis were 0.603 compared to the rtable level of significance 5% N = 76 of 0.2227 so rcount was large from rtable, it can be concluded that the null hypothesis (Ho) is rejected and (Ha) is accepted. With a coefficient of determination of 36.3%, it has a positive effect, meaning that if you use google classroom media it will improve student learning outcomes in Civics subjects at SMA Negeri 1 Kampar. While 63.7% is a factor that affects the Y variable from other factors not examined by the study. Key Words: Influence, Google Classroom, Learning Outcomes, PKN